Mechanics of Micro- and Nano-Size Materials and Structures - Malikan, Mohammad; Dastjerdi, Shahriar (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
For this reprint, we intend to cover theoretical as well as experimental works performed on small scale to predict the material properties and characteristics of any advanced and metamaterials. New studies on mechanics of small-scale structures such as MEMS/NEMS, carbon and non-carbon nanotubes (e.g., CNTs, Carbon nitride, and Boron nitride nanotubes), micro/nano-sensors, nanocomposites, macrocomposites reinforced by micro-/nano-fillers (e.g., graphene platelets), etc., are included in this reprint.